Translation Technique of Taboo Words in ‘Peaky Blinders Season 2 Episode 6’ Indonesian Subtitle and its Impact on the Subtitle Readability - Adhillah Pratiwi Octaviyanti; Agus Salim Mansyur; Dian Budiarti (Prodi Tadris Bahasa Inggris, 2025)
The purpose of this research is to identify the translation techniques applied in translating taboo words in the subtitle of Peaky Blinders Season 2 Episode 6 and to evaluate the readability of the translation. Using a qualitative method, data were collected from two primary sources: the subtitles of the episode and informants through Focus Group Discussions and questionnaires. The findings reveal that 9 types of taboo words were identified; cursing (25), epithets (17), insults and slurs (10), blasphemy (4), obscenity (3), slang (2), profanity (1), vulgarity (1), and scatology (1). Four translation techniques were applied: censorship (32), substitution (11), taboo for taboo (13), and euphemism (8). The average readability score of 2.85 indicates that the translation techniques employed positively impact subtitle readability. This study contributes to the field of translation by exploring how different translation techniques of taboo words affect subtitle readability. The study fills a gap by specifically focusing on taboo word translation using Davoodi's (2009) theory, which is distinct from the general translation technique approaches used in previous studies. The results highlight the importance of selecting appropriate techniques to ensure a comprehensive translations for the audience.